Systemic Myostatin Inhibition via Liver-Targeted Gene Transfer in Normal and Dystrophic Mice - Morine, Kevin J. (Public Library of Science, 2010)
BACKGROUND: Myostatin inhibition is a promising therapeutic strategy to maintain muscle mass in a variety of disorders, including the muscular dystrophies, cachexia, and sarcopenia. Previously described approaches to blocking myostatin signaling include injection delivery of inhibitory propeptide domain or neutralizing antibodies. METHODOLOGY/PRINCIPAL FINDINGS: Here we describe a unique method of myostatin inhibition utilizing recombinant adeno-associated virus to overexpress a secretable dominant negative myostatin exclusively in the liver of mice. Systemic myostatin inhibition led to increased skeletal muscle mass and strength in control C57 Bl/6 mice and in the dystrophin-deficient mdx model of Duchenne muscular dystrophy. The mdx soleus, a mouse muscle more representative of human fiber type composition, demonstrated the most profound improvement in force production and a shift toward faster myosin-heavy chain isoforms. Unexpectedly, the 11-month-old mdx diaphragm was not rescued by long-term myostatin inhibition. Further, mdx mice treated for 11 months exhibited cardiac hypertrophy and impaired function in an inhibitor dose–dependent manner. CONCLUSIONS/SIGNIFICANCE: Liver-targeted gene transfer of a myostatin inhibitor is a valuable tool for preclinical investigation of myostatin blockade and provides novel insights into the long-term effects and shortcomings of myostatin inhibition on striated muscle.